Factors Affecting Success and Failure of Producers Co-ops in Ardabil Province - R Abasi; B Rasoolzadeh; P Abasi (تعاون و کشاورزی, 2010)
This study, conducted in Ardabil Province in 2007, is an attempt to make known thorough a holistic approach those personal, behavioral, organizational and structural factors that are responsible for failures in co-operatives. The universe constituted of 521 members from 173 co-operatives both active and dormant. Also, descriptive statistics, diagnostic analysis, and regression analysis were used for data analysis. Results obtained from diagnostic analysis well revealed that independent variables, including level of participation, satisfaction with the co-op’s performance, collaboration, sympathy, satisfaction with the Board, accountability, interest of members in their own co-op, confidence, manner of managing, emotional relations, and justifiability of the members are all involved in the co-op’s success. Also, findings from regression analysis indicated that some other variables, including participation, easy marketing, using technology, social capital, family participation and high-priced inputs are responsible for bath success and failure. Accordingly some recommendations are made: reinforcing social capital and common norms in co-ops; making activities clear; providing co-ops with management training; creating consultative and monitoring units for providing scientific and technical services; initiating and developing a master plan for marketing processes; establishing marketing co-ops; creating effective linkages among co-ops for product marketing; offering mutual financial, technical and information services; and organizing modular training courses for the educated staff working in co-operative departments at provincial level.